Doubly Heavy Baryon Production in e＋e- Annihilation - 杨中娟 张培峰 郑亚娟 (Chinese physics letters, 2014)
Considering the inclusive process, we study the doubly heavy baryon ≡cc （≡bb） production through e＋e- anni- hilation. Both the diquark QQ in color sextet and triplet are discussed. The results show that the contributions from these two color states play equally important roles. At the Z^0 pole, a significant enhancement can be found in the doubly heavy baryon production.